STRATEGI PENGEMBANGAN AGRIBISNIS BERBASIS PETANI SWADAYA KELAPA SAWIT - Pangestu, Indra Tri; Kusnandar, Kusnandar; Fajarningsih, Rhina Uchyani (Program Studi Agribisnis Fakultas Pertanian, 2025)
Oil palm is a strategic commodity that plays an important role in the Indonesian economy. This study aims to formulate a strategy for developing oil palm independent smallholder-based agribusiness in Ogan Komering Ilir District, South Sumatra. The research was conducted in Ogan Komering Ilir Regency, conducted in August 2024. The research was conducted using key informants. Data collection methods were carried out by means of observation, interviews, documentation and literature studies. The data analysis method uses SWOT Analysis and Analytical Network Process (ANP). Research results that infrastructure development, utilization of human resource quality, and improvement of management capacity are the main priorities in supporting the sustainability and competitiveness of independent smallholders. The results of this study provide strategic recommendations for stakeholders in optimizing the potential of oil palm agribusiness in a sustainable manner.